2015
DOI: 10.1242/jcs.161414
|View full text |Cite
|
Sign up to set email alerts
|

Impaired maturation of large dense-core vesicles in muted-deficient adrenal chromaffin cells

Abstract: The large dense-core vesicle (LDCV), a type of lysosome-related organelle, is involved in the secretion of hormones and neuropeptides in specialized secretory cells. The granin family is a driving force in LDCV biogenesis, but the machinery for granin sorting to this biogenesis pathway is largely unknown. The mu mutant mouse, which carries a spontaneous null mutation on the Muted gene (also known as Bloc1s5), which encodes a subunit of the biogenesis of lysosome-related organelles complex-1 (BLOC-1), is a mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…Our recent results have shown that different subunits of BLOC-1, such as dysbindin, muted, and BLOS1, may have unique functions in lysosomal trafficking (e.g. in endo-lysosomal trafficking, LRO biogenesis, and autophagy) mediated by specific interacting partners (Hao et al, 2015; Wang et al, 2014; Yuan et al, 2015; Zhang et al, 2014a). In addition, BLOS2 may have a function in the nucleus (Sun et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Our recent results have shown that different subunits of BLOC-1, such as dysbindin, muted, and BLOS1, may have unique functions in lysosomal trafficking (e.g. in endo-lysosomal trafficking, LRO biogenesis, and autophagy) mediated by specific interacting partners (Hao et al, 2015; Wang et al, 2014; Yuan et al, 2015; Zhang et al, 2014a). In addition, BLOS2 may have a function in the nucleus (Sun et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The rat monoclonal antibody to human α-synuclein (15G7) was obtained from Alexis Biochemicals 52 , the mouse monoclonal antibody to rodent α-synuclein (Syn-1) from BD Biosciences 53 , the the goat polyclonal antibody to TOM20 (C-20) from Santa Cruz Biotechnology 54 , the guinea pig polyclonal antibody to vesicular glutamate transporter 1 (VGLUT1) from EMD Millipore 55 and the rabbit polyclonal antibodies to secretogranin II (K55101R) from Meridian Life Science 56 and to actin (A2066) from Sigma 57 . The H3C antibody to synuclein developed by J. George was obtained from the Developmental Studies Hybridoma Bank, created by the NICHD of NIH and maintained at the University of Iowa, Department of Biology, Iowa City, IA 52242.…”
Section: Methodsmentioning
confidence: 99%
“…Immature DCVs bud off from the trans‐Golgi and undergo several maturation steps, including homotypic fusion with other immature DCVs, vesicle acidification, peptide processing and sorting of cargos . In recent years, a small but growing number of proteins have been identified as playing roles in DCV biogenesis, beginning to shed some light on the molecular mechanisms underlying the steps in DCV maturation . In one approach to identifying proteins important for DCV biogenesis, genetic screens were performed in Caenorhabditis elegans .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In recent years, a small but growing number of proteins have been identified as playing roles in DCV biogenesis, beginning to shed some light on the molecular mechanisms underlying the steps in DCV maturation. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] In one approach to identifying proteins important for DCV biogenesis, genetic screens were performed in Caenorhabditis elegans. [19][20][21][22][23][24][25] These screens identified several molecules important for early stages of DCV biogenesis and maturation, including the small G-protein RAB-2 and several RAB-2 effectors, including the conserved coiled-coil protein CCCP-1.…”
Section: Introductionmentioning
confidence: 99%